Imobilização da lacase em nanocelulose bacteriana: otimização e avaliação na biotransformação de compostos fenólicos - Reis, Hélen Cristina Oliveira dos (2020)
Biological treatment through the application of enzymes may be an interesting alternative considering it is an efficient, economic and environmentally friendly alternative. Regarding the pollutants of interest in bioremediation, phenolic compounds can be mentioned, due the fact the problem involving these compounds is due to their low degradability and high toxicity in the environment. Among the enzymes that can be used in the bioremediation process, laccase can be presented as a possibility for the degradation of persistent compounds, because, it requires only oxygen for degradation to occur. Therefore, this work aimed to immobilize a Myceliophthora thermophila laccase in bacterial nanocellulose (BNC) for the biotransformation of phenolic compounds aiming at greater operational stability and the possibility of reuse, thus favoring its potential application under industrial operating conditions. The immobilization support, BNC, is a biopolymer produced by some species of bacteria that has several advantages such as biodegradability, high surface area, mechanical strength and flexibility, among others. Therefore, for this work, first it was produced the nanocellulose then the purification process was performed só the nanocellulose could pass to the lyophilization process. Then, a Box-Behnken experimental design was designed in order that the laccase could be immobilized by the cross-linking method. This design focused on the optimization of the immobilization process by evaluating the pH variation (3, 4 and 5), enzyme concentration. (200, 350 and 500 U L-1) and concentration of glutaraldehyde (0.125%, 0.5% and 0.875%). The optimized immobilization condition was at pH 5, enzyme concentration of 200 U L-1 and glutaraldehyde concentration of 0.4%. Immobilization occurred in three stages: (1) adsorption phase in which 10 mg ± 1 BNC was added to tubes containing 10 mL laccase for 30 minutes at 150 rpm at 30 ° C, (2) addition of glutaraldehyde to pass through a static phase at 4°C during overnight and (3) the tubes containing the laccase and BNC solution were rotated at 150 rpm for two hours at 30°C. Subsequently, the immobilization process was performed to determine the optimal conditions for enzyme activity of the free and immobilized laccase using 2,2’-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) as substrate, where the best conditions were observed at pH 4 and 60°C. Then the tests were performed to determine the kinetic parameters, thermal stability, free and immobilized enzyme storage and reuse of the immobilized enzyme, all tests performed in triplicates and using the previously defined optimal conditions. Regarding storage test, the immobilized laccase maintained its relative activity between 90 and 70% after four weeks, while free enzyme maintained after four weeks 40% of its activity. As for the reuse, the immobilized enzyme maintained the relative activity in about 60% and 37% in the fourth cycle and in the last cycle (seventh), respectively. Lastly, the immobilized enzyme showed promising results for being used as detector (biosensor) for catechol considering the fact that even after 90 minutes, it was still possible to detect it by UVVIS also as a support with antioxidant properties regarding the interaction laccase and ferulic acid, being possible to retain 50% of the antioxidant activity of acid ferulic (15 mM), besides the possibility of the biocoloration process.